Enhancing highland ecosystems in East Hararge, Ethiopia: evaluating intervention strategies for species diversity, soil organic carbon stock, and carbon sequestration - Bogale, Daba (Forest science and technology, 2024)
Forest loss and soil degradation pose significant challenges globally, particularly in developing nations like Ethiopia. Various intervention strategies have been implemented to rehabilitate degraded ecosystems. However, research gaps exist in understanding the most effective approaches, particularly in highland ecosystems. This study aimed to evaluate the effectiveness of different intervention strategies on species diversity and carbon stock in the West Hararghe zone, specifically at the Doba district Hades site. The data was collected from 5 February 2022 to 10 December 2022. The study area was characterized by systematic plots and transects to assess vegetation diversity and soil properties across four intervention categories: (physical; only soil and water conservation structures were used, enclosure; only animal and human interaction was restricted, biological; only different tree species were planted, biophysical; both soil water conservation and tree planting were used). Soil samples were collected at different depths, and biomass estimation was conducted using established formulas. Statistical analyses, including one-way ANOVA and post-hoc tests, were performed to test the level of significance. Biophysical interventions exhibited the highest species diversity index (SDI) (4.65 ± 1.21), followed by enclosure interventions (1.68 ± 0.58), while physical interventions recorded the lowest SDI (0.63 ± 0.18). Enclosure interventions led to the highest soil organic carbon (SOC) stocks at 40.13 t C ha −1 , followed by biophysical interventions at 39.26 t C ha −1 . Physical interventions resulted in the lowest SOC stocks at 23.9 t C ha −1 , underscoring their potential for carbon sequestration. Biophysical interventions, which include both above-ground and below-ground biomass, showed significant carbon stock accumulation, totaling 173.8 t C ha −1 (39.26 t C ha −1 from SOC and 114.6 t C ha −1 from biomass), highlighting their effectiveness in enhancing ecosystem resilience. Other studies support these findings, underscoring the importance of context-specific approaches and long-term monitoring for sustainable land management. Enclosure and biophysical interventions emerge as promising strategies for enhancing species diversity and soil health, as well as promoting carbon sequestration in highland ecosystems. These findings emphasize the need for informed decision-making and community involvement in ecosystem restoration efforts to achieve meaningful and lasting impacts.